Functional Reconstruction of a Combined Tendocutaneous Defect of the Achilles Using a Segmental Rectus Femoris Myofascial Construct: A Viable Alternative - DeFazio, Michael Vincent; Han, Kevin Dong; Evans, Karen Kim (Archives of Plastic Surgery, 2014)
The composite anterolateral thigh flap with vascularized fascia lata has emerged as a workhorse at our institution for complex Achilles defects requiring both tendon and soft tissue reconstruction. Safe elevation of this flap, however, is occasionally challenged by absent or inadequate perforators supplying the anterolateral thigh. When discovered intraoperatively, alternative options derived from the same vascular network can be pursued. We present the case of a 74-year-old male who underwent composite Achilles defect reconstruction using a segmental rectus femoris myofascial free flap. Following graduated rehabilitation, postoperatively, the patient resumed full activity and was able to ambulate on his tip-toes. At 1-year follow-up, active total range of motion of the reconstructed ankle exceeded 85% of the unaffected side, and donor site morbidity was negligible. American Orthopaedic Foot and Ankle Society and Short Form-36 scores improved by 78.8% and 28.8%, respectively, compared to preoperative baseline assessments. Based on our findings, we advocate for use of the combined rectus femoris myofascial free flap as a rescue option for reconstructing composite Achilles tendon/posterior leg defects in the setting of inadequate anterolateral thigh perforators. To our knowledge, this is the first report to describe use of this flap for such an indication.
Keywords: Achilles tendon; Composite tissue allografts; Free tissue flaps; Patient outcomes assessment; Quadriceps muscle